2023
DOI: 10.1111/jcpp.13847
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐lagged twin study of emotional symptoms, social isolation and peer victimisation from early adolescence to emerging adulthood

Abstract: BackgroundEmotional symptoms, such as anxiety and depressive symptoms, are common during adolescence, often persist over time, and can precede the emergence of severe anxiety and depressive disorders. Studies suggest that a vicious cycle of reciprocal influences between emotional symptoms and interpersonal difficulties may explain why some adolescents suffer from persisting emotional symptoms. However, the role of different types of interpersonal difficulties, such as social isolation and peer victimisation, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Avoidant emerging adults are believed to be not only disinterested in social interactions (in contrast to their shy counterparts), but also prone to actively avoiding opportunities for peer interaction (in contrast to their unsociable counterparts) [11]. Some researchers have proposed that social avoidance might derive from high levels of social anxiety felt during exposure to negative peer experiences, such as rejection or victimization [31]. Others have suggested that this socially withdrawn subtype may represent a highly severe form of shyness [11].…”
Section: Motivations For Social Withdrawalmentioning
confidence: 99%
See 2 more Smart Citations
“…Avoidant emerging adults are believed to be not only disinterested in social interactions (in contrast to their shy counterparts), but also prone to actively avoiding opportunities for peer interaction (in contrast to their unsociable counterparts) [11]. Some researchers have proposed that social avoidance might derive from high levels of social anxiety felt during exposure to negative peer experiences, such as rejection or victimization [31]. Others have suggested that this socially withdrawn subtype may represent a highly severe form of shyness [11].…”
Section: Motivations For Social Withdrawalmentioning
confidence: 99%
“…Shyness is a relatively stable temperamental trait throughout development [11]. It is also robustly related to internalizing problems (e.g., negative affect, social anxiety, loneliness) and peer difficulties (e.g., rejection, victimization) from early childhood through emerging adulthood [31,33]. Among emerging adults, shyness has demonstrated associations with depressive symptoms, existential concerns, test anxiety, and lower levels of academic self-efficacy [16,34].…”
Section: Implications Of Motivations For Social Withdrawal In Emergin...mentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant focus of mental health research and practice is on understanding the pathogenic basis of the development of psychiatric disorders and on interventions to reduce the distress and functional impairments that are often experienced by people diagnosed with these disorders. These remain admirable and essential aims and indeed many of the papers in this issue of the Journal provide useful insights into factors that predict the onset and persistence of psychopathology (Defoe, Treffers, & Stams, 2023;Morneau-Vaillancourt et al, 2023;Shakeshaft et al, 2023;Taylor et al, 2023) and evaluate interventions to treat symptoms and associated difficulties (Moerkerke et al, 2023). However, it could be argued that there is little to be gained from continuing to fan the pathogenic flames of psychiatry as this would likely only lead to incremental advances in understanding the aetiology and treatment of psychiatric disorders.…”
mentioning
confidence: 99%